2014
DOI: 10.1152/ajpgi.00382.2013
|View full text |Cite
|
Sign up to set email alerts
|

Key role of endothelial importin-α in VEGF expression and gastric angiogenesis: novel insight into aging gastropathy

Abstract: Ahluwalia A, Jones MK, Tarnawski AS. Key role of endothelial importin-␣ in VEGF expression and gastric angiogenesis: novel insight into aging gastropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 39 publications
2
40
0
Order By: Relevance
“…AGECs had a significantly reduced in vitro angiogenesis and VEGF protein expression (Fig. ) compared with YGECs (both P < 0.001) . Furthermore, exogenous VEGF treatment increased in vitro angiogenesis in AGECs by 2.3‐fold ( P < 0.001) (Fig.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…AGECs had a significantly reduced in vitro angiogenesis and VEGF protein expression (Fig. ) compared with YGECs (both P < 0.001) . Furthermore, exogenous VEGF treatment increased in vitro angiogenesis in AGECs by 2.3‐fold ( P < 0.001) (Fig.…”
Section: Introductionmentioning
confidence: 80%
“…Importin‐α is a nuclear transport protein and mediates nuclear import of cargo proteins . In a recent study, we demonstrated the critical role of importin‐α in angiogenesis in gastric mucosal ECs . The downregulation of importin‐α1 and importin‐α3 in gastric mucosal ECs using specific siRNA significantly reduced in vitro angiogenesis (by 93%) and VEGF mRNA expression levels (by 52%) .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another study reported that the inhibition of cell proliferation promoted by PAR-4 might be mediated by the ERK1/2 pathway (Pereira et al, 2013). KPNA4 (karyopherin alpha 4, importin alpha 3) regulated angiogenesis and VEGF expression (Ahluwalia et al, 2014). Combining the published data with our results of IPA analysis, we speculate that miR-181c might regulate cell proliferation, apoptosis, angiogenesis and lipid metabolism in the priming phase of rat LR by targeting PAWR, KPNA4, FKBP1A and CROT through NF-κB, ERK1/2 and mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, KPNA4 is a potential target for cancer therapy at least through its regulation of NF-κB and Notch signaling. A link between the KPNA family and gastric angiogenesis has been demonstrated in a model of gastric mucosal endothelial cells in vitro , in which the expressions of KPNA2 and KPNA4 were associated with the production of VEGF (25). In addition, MiR-181s have been identified as negative regulators of mesenchymal transition in glioblastoma by targeting KPNA4 (26), and miR-181a regulates prostate cell migration and invasion (27), indicating a potential link between KPNA4 and cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%